HCN polymers characterized by solid state NMR: Chains and sheets formed in the neat liquid - Mamajanov, Irena (American Institute of Physics, 2009)
Hydrogen cyanide polymerizes readily under a variety of conditions and significant prebiotic roles have been suggested for these polymers due to the abundance of HCN in universe. However, the structures of HCN polymers have been more speculative than grounded in experimental data. Here we show that (13)C and (15)N solid state NMR spectra of polymers formed in neat HCN are inconsistent with the previously proposed structures and suggest instead that the polymers are formed by simple monomer addition, first in head-to-tail fashion to form linear, conjugated chains, and then laterally to form saturated two-dimensional networks. This interpretation of the NMR spectra finds support in other information about the polymerization of neat HCN, including the presence of free radicals. As expected from the literature, formation of the HCN tetramer, diaminomaleonitrile, is also observed, but only when the reaction is catalyzed exclusively by base and then in crystalline form.